Gamification for Increasing Learning Motivation of College Student - Agnes Kurniati; Francisco Maruli Panggabean; Nadia Nadia; Thomas Galih Satria (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
The purpose of this research is to build an attractive gamification system that could motivate college students as the user target by customized challenges with adjustable difficulty-scaled reward systems. The methods used for the research consists of problem identification, collecting and analyzing the data, problem formulation, solution and design creation, product implementation, and evaluation. StudyGO is a mobile application that has 2 main features that have gamification aspects which are focused and scheduled study. The application evaluation is done with questionnaire evaluation based on 5 measurable human factors. The majority results from the application feels very motivated and rewarded enough from this gamification system.